A Comparison of Levelised Cost of Energy of Different Energy Sources for Irrigated Shallot Farming in Some Coastal Regions of Ghana - Saeed Abdul-Ganiiyu; Rosa Emefa Djangba; Denis Edem Kwame Dzebre; David Ato Quansah; Muyiwa Samuel Adaramola (Journal of Applied Engineering and Technological Science (JAETS), 2024)
This study assessed the technical and economic viability of Poldaw wind pumps for irrigates shallot cultivation in the Keta Municipality in Ghana. Technical analyses of 4 versions of the Poldaw pump is conducted to determine if it they can supply the water requirements for irrigated shallot farming. The Levelized Cost of Energy (LCOE) of wind energy for irrigation over a period of 20 years is also calculated and compared with that of grid electricity, diesel, petrol and premix fuels as alternative energy sources for irrigated shallot farming in the area. At a hub height of 10 m, the 5.0 m Poldaw was found to be capable of supplying the daily water requirements for irrigated shallot farming in the area. In addition, its LCOE is better than those of petrol, diesel and premix fuel. Grid electricity lost its slight advantage on LCOE when the Poldaw pump was assessed for hub heights of 12 m and higher. The findings of the study suggest that the 5.0 m Poldaw pump is a viable alternative to pumps powered by other energy sources currently used for irrigated shallot farming in the Municipality.